Kandungan dan Serapan Mineral Pucuk Indigofera zollingeriana dari Tanaman dengan Kerapatan Tanam Berbeda: Mineral Content and Uptake of Indigofera zollingeriana on Different Planting Densities - Azib Ernawati -; Luki Abdullah; Idat Galih Permana (Departemen Ilmu Nutrisi dan Teknologi Pakan Fakultas Peternakan Institut Pertanian Bogor, 2021)
This experiment was conducted to evaluate the mineral contents of I. zollingeriana growing with different planting densities. The experiment was conducted in a randomized block design with three different planting densities (8,000 plants per ha, 13,333 plants per ha, and 20,000 plants per ha) and 3 replication. Plant biomass was analyzed for macro and micro mineral contents as well as Ca:P ratio. The results showed that increased planting densities significantly increased (p<0.05) P, Cu, and Cr contents, but decreased Ca and Na contents had no significant effect on Mg, K, Mn, Zn and Fe contents. Furthermore, the increased planting densities significantly decreased (p<0.05) uptakes of Ca, K, Mn, and Fe by the plants, but increased (p<0.05) the uptakes of Cu and Cr. Meanwhile, the uptakes of P, K, Na, and Zn were not affected by planting densities. Based on the results of this study, it can be concluded that the planting density of I. zollingeriana should be maintained in 8,000 plants ha-1 to maintain the content and uptake of mineral in forage crops. Key words: defoliation periods, Indigofera zollingeriana, macrominerals, micro minerals, planting density